STRATEGI PERPUSTAKAAN SEKOLAH SMK NEGERI 4 MALANG DALAM MENYEDIAKAN SUMBER INFORMASI UNTUK SISWA - Ganis Chandra Puspitadewi; Fiki Sabri Irawan (JURNAL ILMU PERPUSTAKAAN (JIPER), 2023)
The Library SMK Negeri 4 Malang is a source of information required to provide librarians with access to library services and collections. This study seeks to identify and describe the SMK State 4 Malang school library's strategy for serving as a source of information for students. The library at SMC State 4 Malang serves as the location for qualitative research employing descriptive methods. Techniques for data collection using structured interviews According to the results of the research, there are ten major findings in the process and strategy of providing information sources in the school library of SMK Negeri 4 Malang. These include the collection of information resources available in the library, the strategy or effort of a library in providing information sources to students, the reasons for the existence of a strategy or attempt to provide information resources in the libraries, the attitude of librarians i.e., their willingness to provide information sources to students, and the attitude of librarians. The anticipated strategies and efforts can be effectively implemented. A significant number of students are pleased to use the library's services and take advantage of the collection that has been made available